If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2=z-3
We move all terms to the left:
2-(z-3)=0
We get rid of parentheses
-z+3+2=0
We add all the numbers together, and all the variables
-1z+5=0
We move all terms containing z to the left, all other terms to the right
-z=-5
z=-5/-1
z=+5
| 14=s+1 | | -3(7x-2)=20 | | -3x-28=24-5x | | n+1.1=9.6 | | 3/2(x-4)=-4+1/3x | | -x/6=48 | | 19=42–x | | 4z=14+-38 | | 19=42−x | | 8x+20x=-20 | | 2x-5+3x-25+5x+45=180 | | B(x)=50.00-0.05x | | 3(x-1)+5x-6=540 | | m-33=-32 | | 392a+1)-7=50 | | 5x+8=-(5×-8) | | 4y-13=47 | | 1/2(3x-6)=-9 | | 8/3k=2/5 | | 87=5x-13 | | 7(3w−=5) | | 15x-15=21+14x | | 4x+7=64° | | 2(r+7)=36 | | 5y(y+4)=6y | | 6(u-8)=9u-27 | | 2(2–x)=4(–2+x) | | 3x+x-35=180 | | -(x-9)^2=64 | | -79-6x=137+3x | | 3/4x+8=1/4x+6 | | 100+15x=65+20x |